The Relationship between Bladder, Periarterial and Somatic Neuropathy in Diabetes - Sakakibara, Ryuji (Intern Med, 2018)
OBJECTIVE: Diabetes commonly affects the bladder nerves. However, the relationship among bladder, periarterial and somatic neuropathy in diabetes is not well known. In the present study we investigated these relationships. METHODS: A total of 110 diabetic subjects were enrolled in the study. All were referred for screening for diabetic neuropathy, irrespective of their symptoms. The patients included 61 men and 49 women; the mean age was 59.3 years (31-85 years); the mean disease duration was 14.0 years (5-30 years); and the mean HbA1c value was 10.1% (5.1-16.3%). We performed a nerve conduction study (NCS, A-alpha/beta and B fiber), ultrasound-based measurement of the post-void residual (PVR) volume (abnormal, >50 mL, mainly A-delta/C fiber) and postural blood pressure measurement (abnormal, >-20 mmHg, A-delta/C fiber). Fisher's exact probability test and Student's t-test were used to analyze the significance of differences. RESULTS: NCS abnormality, an abnormal PVR volume, and postural hypotension were noted in 74, 19, and 36 of the subjects, respectively. There were clear relationships between NCS and an abnormal PVR volume (p<0.05), postural hypotension and an abnormal PVR volume (p<0.05), or NCS and postural hypotension (p<0.01). There were also subjects who had NCS abnormality alone, a high PVR volume alone or postural hypotension alone. An abnormal PVR volume was not associated with the HbA1c value, but was clearly related to the duration of diabetes (p<0.05). CONCLUSION: Bladder dysfunction was correlated with somatic and periarterial neuropathy. On the other hand, 16% of the cases of bladder dysfunction occurred in patients without somatic or periarterial neuropathy; thus, the regular measurement of the PVR volume is necessary.